Pancreatic islet β-cell subtypes are derived from biochemically-distinct and nutritionally-regulated islet progenitors - Monica E. Brown; Verda E. Miranda; Simone Nevills; Ruiying Hu; Prasanna K. Dadi; Alan J. Simmons; Yanwen Xu; Yilin Yang; Mahircan Yagan; Sadia Najam; Leesa L. Sampson; Mark A. Magnuson; et al. (Nature Communications)
Abstract Endocrine islet β cells comprise heterogenous subtypes with different gene expression and function levels. Here we study when/how this heterogeneity is induced and how long each subtype maintains its characteristic properties. We show that islet progenitors with distinct gene expression and DNA methylation patterns produce β-cell subtypes of different secretory function, proliferation rate, and viability in male and female mice. These subtypes have differential gene expression that regulates insulin vesicle production or stimulation-secretion coupling and differential DNA methylation in the putative enhancers of these genes. Maternal obesity, a major diabetes risk factor, reduces the proportion of the β-cell subtype with higher levels of glucose responsiveness. The gene signature that defines mouse β-cell subtypes can reliably divide human cells into two sub-populations, with the one having higher predicted glucose responsiveness reduced in diabetic donors. These results suggest that β-cell subtypes can be derived from islet progenitor subsets modulated by maternal nutrition.